The mating game : how gender still shapes how we date - Lamont, Ellen, 1979- (University of California Press, 2020)
"Despite enormous changes in patterns of dating and courtship in twenty-first-century America, contemporary understandings of romance and intimacy remain firmly rooted in assumptions of gender difference. Yet these beliefs now vie with new cultural messages of gender equality that stress self-development, independence, and egalitarian practices in public and private life. Through interviews with heterosexual and LGBTQ individuals, Ellen Lamont's The Mating Game explores how people with diverse sexualities and gendered identities date, form romantic relationships, and make decisions about future commitments as they negotiate an uncertain romantic landscape fraught with competing messages about gender, sexuality, and intimate relationships"--